2017
DOI: 10.3390/chemengineering1020017
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Depolymerization of Lignin Using Supported Niobium Catalysts

Abstract: Abstract:Valorization of lignin into aromatics has driven researchers for decades. In this research, niobium was deposited on oyster shells (OSNC) and carbon rods (CRNC) and tested as a catalyst for depolymerization of lignin. Catalysts (2%, 5%, and 8% loading) were synthesized via wet impregnation. Batch experiments were performed at 95 • C, using 8 g of lignin, and 1 g of catalyst. Our research indicates that niobium supported catalysts are effective in partial oxidation of lignin. Maximum vanillin concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Oxidative approaches to lignin depolymerization, especially utilizing molecular oxygen, hydrogen peroxide, peroxyacids or ozone, have a great potential to become important and economically viable lignin delignification technologies [17], as the reaction pathways can yield valuable chemicals such as simple aldehydes (vanillin, syringaldehyde, p-hydroxybenzaldehyde) or acids (vanillic acid and syringic acid) [18]. Depending on the extent of oxidation, various carboxylic acids having aromatic and non-aromatic structures with mono-or di-carboxyl functional groups can be produced [19].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative approaches to lignin depolymerization, especially utilizing molecular oxygen, hydrogen peroxide, peroxyacids or ozone, have a great potential to become important and economically viable lignin delignification technologies [17], as the reaction pathways can yield valuable chemicals such as simple aldehydes (vanillin, syringaldehyde, p-hydroxybenzaldehyde) or acids (vanillic acid and syringic acid) [18]. Depending on the extent of oxidation, various carboxylic acids having aromatic and non-aromatic structures with mono-or di-carboxyl functional groups can be produced [19].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison studies revealed that nitrobenzene oxidation process gave higher yields of vanillin than the alkaline aerobic oxidation processes. Surprisingly, adding H 2 O 2 to the reaction mixture led to decreased vanillin production over supported Nb catalysts, caused by further oxidation of vanillin [47].…”
Section: Acetal Formation-assisted Delignification Followed By Cataly...mentioning
confidence: 98%
“…There are two different methods of degradation of lignin; one is oxidative and another is reductive. With the help of these methods, lignin is transformed into useful organic compound (Das et al , 2017; Lange et al , 2013; Luo et al , 2016; Nanayakkara et al , 2014; Yanez et al , 2018). These lignin transformations have been used in dye removal (Kong et al , 2015), photo-responsive applications (Duval et al , 2015) and for removal of heavy metals from water (Jin et al , 2017).…”
Section: Introductionmentioning
confidence: 99%